Role of Political Parties in Public Policy Decision - Chaerul Umam; Widayati Widayati; Rakhmat Bowo Suharto (Law Development Journal, 2021)
This research aims to analyze the ability of the role of political parties in determining public policies, and also to analyze suitable solutions to be implemented. This research approach method uses normative juridical. The specification of this research uses qualitative analytical descriptive, and the source material uses primary and secondary legal materials, and uses the theory of democracy, the theory of rule of law, the theory of political parties, and the theory of public policy. Based on the research, it can be concluded that the problem arises with the existence of party power that is too strong in all elements, for example in parliament where there is a recall right from a political party which is not based on the cadre's performance in parliament but based on the policy the cadre takes is not a party policy. Improving the internal system is a step that must be taken to improve the party system, because like the explanation in the third discussion that the strengthening of political party internal regulations should make the democratic system run better, the fact is that research on political party regulations is quite good, but it is necessary. There is an emphasis and realization of these regulations that are often not carried out by the parties themselves.